Macroeconomics & monetary theory - Johnson, Harry G. 1923-1977. 4 0 (Harry Gordon),16; 5 (New Brunswick, N.J. : AldineTransaction, 2007)
An introduction to macroeconomics and classic monetary theory that describes the influence of John Maynard Keynes, and explains Keynesian economics, as well as the major issues in monetary economics, and other related topics.
Reprint. Originally published: Hawthorne, N.Y. : Aldine Pub., 1972.
Includes bibliographical references (p. 198-210).
Adult;Adult
Keywords: 2 -- 0; 6; Money.;Macroeconomics.;Money.;Macroeconomics.; 20; 2